2020
DOI: 10.1021/acs.chemmater.0c01605
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap-Tunable, Chiral Hybrid Metal Halides Displaying Second-Harmonic Generation

Abstract: The introduction of chirality in lead halide perovskites and related metal halide materials allows for an expansion of their unique and useful properties toward nonlinear optics. However, when synthesizing materials based on less toxic metals antimony and bismuth, the large variability in the crystal structures of their metalates and their tendency to form molecular or chainlike anion motifs can be a challenge when creating tunable materials. Here, we show that using a chiral amine template, we can synthesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 75 publications
3
64
0
Order By: Relevance
“…The polarization dependence tests were conducted by rotating the λ /2 plate to generate linearly polarized light with different directions, in which p ‐polarized (parallel to the plane of incidence) input polarization at 0° angle and fixed linear‐polarized output polarization. The polarization plots (Figure 4d) accorded well with cos 4 θ function, [ 40 ] demonstrating the anisotropy of materials with P 2 1 space group [ 50,53 ] (see details in Supporting Information). The polarization ratio defined as ρ = ( I max – I max )/( I max + I max ) is ≈0.83 for a linearly polarized analyzer and suggests a comparably high sensitivity of SHG to the crystal symmetry.…”
Section: Resultssupporting
confidence: 54%
“…The polarization dependence tests were conducted by rotating the λ /2 plate to generate linearly polarized light with different directions, in which p ‐polarized (parallel to the plane of incidence) input polarization at 0° angle and fixed linear‐polarized output polarization. The polarization plots (Figure 4d) accorded well with cos 4 θ function, [ 40 ] demonstrating the anisotropy of materials with P 2 1 space group [ 50,53 ] (see details in Supporting Information). The polarization ratio defined as ρ = ( I max – I max )/( I max + I max ) is ≈0.83 for a linearly polarized analyzer and suggests a comparably high sensitivity of SHG to the crystal symmetry.…”
Section: Resultssupporting
confidence: 54%
“…For example, Xu and co‐workers determined second‐order nonlinear optical (NLO) coefficient of (R‐/S‐MPEA) 1.5 PbBr 3.5 (DMSO) 0.5 (MPEA=β‐methylphenethylamine) as approximately 0.68 pm V −1 at 850 nm [12] . Very recently, a series of chiral metal halides were manufactured by Heine and co‐workers, [13] and the SHG signals were 5–45 times smaller than the quartz reference.…”
Section: Figurementioning
confidence: 99%
“…The organic cations in (TMEDA)SbI 5 and (TMEDA) BiI 5 connect with the adjacent inorganic octahedral chains through hydrogen bonds. This interaction forms a prominently stable structural framework with the higher melting point than some reported OIMHs such as (C 5 H 10 N) 2 BiBr 5 (200 °C), [18] (C 4 H 14 N 2 ) 2 In 2 Br 10 (200 °C), [19] (C 6 H 5 CH 2 NH 3 )InBr 6 (220 °C), [20] (CH 3 NH 3 ) 3 Sb 2 I 9 (253 °C), [21] [22] (C 7 H 7 )BiI 4 (200 °C), and (C 7 H 7 ) SbI 4 (240 °C). [23] Further, the DSC measurement results also indicated that (TMEDA)SbI 5 and (TMEDA)BiI 5 did not undergo a phase change in this temperature range.…”
Section: Resultsmentioning
confidence: 99%